2019
DOI: 10.1002/lt.25469
|View full text |Cite
|
Sign up to set email alerts
|

Physicians’ Perspectives on Palliative Care for Patients With End‐Stage Liver Disease: A National Survey Study

Abstract: Specialty palliative care (PC) is underused for patients with end‐stage liver disease (ESLD). We sought to examine attitudes of hepatologists and gastroenterologists about PC for patients with ESLD. We conducted a cross‐sectional survey of these specialists who provide care to patients with ESLD. Participants were recruited from the American Association for the Study of Liver Diseases membership directory. Using a questionnaire adapted from prior studies, we examined physicians’ attitudes about PC and whether … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 48 publications
3
38
0
Order By: Relevance
“…The majority (69%) of the cohort were male participants, with a median (IQR, interquartile rage) age at study entrance of 59 years (54-69). Median (IQR) MELD score at study entrance was 26 (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32). The most common etiology of ESLD for the study cohort was alcoholic liver disease (47%), followed by non-alcoholic fatty liver disease (22%), alcoholic liver disease and hepatitis C (16%), hepatitis C (6%), and miscellaneous causes (9%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority (69%) of the cohort were male participants, with a median (IQR, interquartile rage) age at study entrance of 59 years (54-69). Median (IQR) MELD score at study entrance was 26 (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32). The most common etiology of ESLD for the study cohort was alcoholic liver disease (47%), followed by non-alcoholic fatty liver disease (22%), alcoholic liver disease and hepatitis C (16%), hepatitis C (6%), and miscellaneous causes (9%).…”
Section: Resultsmentioning
confidence: 99%
“…Others have explored this area and have suggested that these clinicians may not have the skills or confidence to initiate such confronting discussions and may also have difficulty identifying when palliative care referral should occur. [20][21][22] Upskilling The difficulties of clinicians engaging with patients in discussions concerning prognosis is reflected by the lack of documentation of resuscitation status and advanced care directives seen in this study. This finding has also been noted by other investigators who have suggested that discussions regarding prognosis occur infrequently.…”
Section: Discussionmentioning
confidence: 95%
“…34 Available literature in other areas of medicine suggests that clinicians may be reluctant to initiate such discussions when patients are not experiencing severe symptoms, or when they have not exhausted curative treatment options. 55,56 Almost all (90%) patients receiving dialysis in one study reported that their clinicians had not discussed disease prognosis, 57 despite the relatively high annual mortality rate. Clinicians may avoid discussions of prognosis because they are uncertain about prognostic accuracy.…”
Section: Knowledge Gaps In Understanding Clinicians' Experiencesmentioning
confidence: 99%
“…( 23 ) For providers, barriers include uneasiness in including PC consultants, misperception of PC being just end‐of‐life care, insufficient guidelines for PC integration, inadequate access to PC providers coupled with deficiency in the PC‐provider workforce, insufficient time during routine clinical care for complex discussions, inadequate training in goals‐of‐care discussions or psychological/symptom management, and a preferential focus on life‐saving interventions. ( 24 ) Fear of upsetting patients, not wanting to abandon them, considering PC referral as an admission of failure/no hope, patients’ having impaired cognitive capacity to participate in provider‐led discussions, and providers not completely understanding the benefits of PC are other reasons. ( 4 ) For health systems, implementation and policy barriers have been identified.…”
Section: Barriers To Implementing Pcmentioning
confidence: 99%